2004
DOI: 10.5194/angeo-22-1335-2004
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of man-made contamination on ULF measurements

Abstract: Abstract. An analysis of the man made contamination on ULF measurements in highly populated areas has been conducted at several suitably chosen sites in Western Europe. The experimental results show common characteristics at different stations with clear evidence for an additional working day contamination with respect to weekends. These effects more clearly emerge in the vertical component that is less influenced by natural signals. A similar analysis conducted at Terra Nova Bay does not reveal any clear evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
(15 reference statements)
1
7
0
Order By: Relevance
“…Figure 5a-c show the signal behaviour for the entire three days (00:00-24:00 LT) preceding the event: as can be seen, in addition to the well known daily modulation related to ionospheric and magnetospheric processes (less evident in the Pc4-Pc5 bands) as well as to man-made contamination (more explicit at higher frequencies, Villante et al, 2004), the experimental results do not reveal any increase of activity starting few hours before the earthquake (Fraser-Smith et al, 1990;Bernardi et al, 1991;Molchanov et al, 1992). Similarly, the polarization parameter (Fig.…”
Section: The Short Term Behaviormentioning
confidence: 94%
See 1 more Smart Citation
“…Figure 5a-c show the signal behaviour for the entire three days (00:00-24:00 LT) preceding the event: as can be seen, in addition to the well known daily modulation related to ionospheric and magnetospheric processes (less evident in the Pc4-Pc5 bands) as well as to man-made contamination (more explicit at higher frequencies, Villante et al, 2004), the experimental results do not reveal any increase of activity starting few hours before the earthquake (Fraser-Smith et al, 1990;Bernardi et al, 1991;Molchanov et al, 1992). Similarly, the polarization parameter (Fig.…”
Section: The Short Term Behaviormentioning
confidence: 94%
“…The rms of the quantization noise is less than 0.5 pT in the frequency range 1-500 mHz. According to Villante and Vellante (1998) and Villante et al (2004), the man-made contamination determines in the ULF bands a weekly modulation with minimum power values on Sundays and reduced power level on Saturdays; such contamination would provide an additional noise during weekdays (daytime hours) of ∼1 pT (Pc1), ∼2 pT (Pc2), ∼3 pT (Pc3), while no significant contamination was determined in the lower frequency bands and, in general, during nighttime hours.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the possible disappearance (or significant reduction) of the man-made contamination during short intervals in the middle of the night, Villante et al [2004] conducted the same kind of analysis for different time intervals in the nighttime sector.…”
Section: Introductionmentioning
confidence: 99%
“…At this site, ULF measurements have routinely been conducted since 1985, and a previous analysis U. Villante et al: On the man-made contamination on ULF measurements revealed during the period 2000-2002 (104 < R s < 120) a weekly modulation of the ULF power on the vertical component (Z) with minimum values on Sundays (10-20 % smaller than during the week), and some evidence for a similar behavior in the horizontal components H (north-south) and D (east-west) (Villante et al, 2004; see also Villante and Vellante, 1998). Recently, Santarelli et al (2014) considered the daily distribution of the root mean square (rms) of components on a hourly base, selecting intervals with local index K ≈ 0 during the period 2006-2007, and found maximum amplitude around noon in the H component, in the entire morning in the D component, and two maxima at ≈ 06:00 and ≈ 15:00 UT in the Z component.…”
Section: Introductionmentioning
confidence: 99%